Stable Anion‐Derived Solid Electrolyte Interphase in Lithium Metal Batteries - Li, Tao; Zhang, Xue‐Qiang; Yao, Nan; Yao, Yu‐Xing; Hou, Li‐Peng; Chen, Xiang; Zhou, Ming‐Yue; Huang, Jia‐Qi; Zhang, Qiang (Angewandte Chemie International Edition, 2021)
High‐energy‐density lithium (Li) metal batteries are severely hindered by the dendritic Li deposition dictated by non‐uniform solid electrolyte interphase (SEI). Despite its unique advantages in improving the uniformity of Li deposition, the current anion‐derived SEI is unsatisfactory under practical conditions. Herein regulating the electrolyte structure of anions by anion receptors was proposed to construct stable anion‐derived SEI. Tris(pentafluorophenyl)borane (TPFPB) anion acceptors with electron‐deficient boron atoms interact with bis(fluorosulfonyl)imide anions (FSI−) and decrease the reduction stability of FSI−. Furthermore, the type of aggregate cluster of FSI− in electrolyte changes, FSI− interacting with more Li ions in the presence of TPFPB. Therefore, the decomposition of FSI− to form Li2S is promoted, improving the stability of anion‐derived SEI. In working Li | LiNi0.5Co0.2Mn0.3O2 batteries under practical conditions, the anion‐derived SEI with TPFPB undergoes 194 cycles compared with 98 cycles of routine anion‐derived SEI. This work inspires a fresh ground to construct stable anion‐derived SEI by manipulating the electrolyte structure of anions. Directly regulating the electrolyte structure of anions by an anion receptor was proposed for the construction of a stable anion‐derived solid electrolyte interphase (SEI). The introduction of an anion receptor decreases the reduction stability of FSI− and increases the amount of FSI− in the form of AGG‐II. The decomposition of FSI− to form Li2S is promoted, improving the stability of the anion‐derived SEI under practical conditions.